2020
DOI: 10.1080/21623945.2020.1721235
|View full text |Cite
|
Sign up to set email alerts
|

Insulin negatively regulates dedifferentiation of mouse adipocytes in vitro

Abstract: Insulin plays an important role during adipogenic differentiation of animal preadipocytes and the maintenance of mature phenotypes. However, its role and mechanism in dedifferentiation of adipocyte remains unclear. This study investigated the effects of insulin on dedifferentiation of mice adipocytes, and the potential mechanisms. The preadipocytes were isolated from the subcutaneous white adipose tissue of wild type (WT), TNFα gene mutant (TNFα-/-), leptin gene spontaneous point mutant (db/db) and TNFα-/-/db/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Total cellular RNA was isolated from cells at various time points in each group as previously described [ 16 ]. The primers used in this study are shown in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total cellular RNA was isolated from cells at various time points in each group as previously described [ 16 ]. The primers used in this study are shown in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of adipocyte AKT causes severe WAT atrophy, and was accompanied by insulin resistance and other metabolic syndrome phenotypes [ 15 ]. Our previous study showed that insulin signalling negatively regulates humans and mice WACs dedifferentiation through the PI3K-AKT-mTORC1 signalling pathway [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…But the pAKT level in de‐differentiation was lower than that in differentiation. Further, blocking the insulin signal decreased the pAKT level (Zang et al, 2020). This suggests that insulin/AKT signaling does play a vital role in preventing adipocyte de‐differentiation (Figure 3).…”
Section: Factors Involved In Adipocyte De‐differentiationmentioning
confidence: 99%
“…Considering the key role of insulin in adipocyte differentiation, researchers speculate that it may also regulate de‐differentiation (El‐Chaâr et al, 2004; Zang et al, 2020). In mature adipocytes, insulin deficiency leads to decreasing lipid droplets and the emergence of fibroblast‐like cells resembling undifferentiated adipocytes.…”
Section: Factors Involved In Adipocyte De‐differentiationmentioning
confidence: 99%
See 1 more Smart Citation